(untitled) - Anthony, William P.; William P. Anthony; K. Michele Kacmar; Pamela L. Perrewé (Fort Worth, 2006)
This popular text written from a "what human resources can do for you" perspective, demonstrates how human resources fit into the organizational big picture. Many cross-functional topics are integrated throughout the text including, marketing, finance, operations, and accounting. Updated cases include material that reinforces the key concepts presented in the text and provides an additional practical perspective to problems faced by human resource managers. The market includes all universities that teach a course in Human Resource Management. It may be used for both upper-division undergraduate and graduate level courses
Keywords: Personnel management